2003
DOI: 10.1007/s00442-003-1332-2
|View full text |Cite
|
Sign up to set email alerts
|

The relative importance of sexual reproduction versus clonal spread in an aridland bunchgrass

Abstract: Festuca idahoensis (Idaho fescue) is a perennial caespitose grass, common in semi-arid rangelands of the Intermountain West. To determine how individuals are recruited into a population, we studied two long-term monitoring plots that were established in 1937 at the Northern Great Basin Experimental Range in southeastern Oregon. The plots measured 3.05x3.05 m, and were located approximately 30 m apart. One plot was ungrazed, the other was subject to moderate levels of cattle grazing. The number of F. idahoensis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
2
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 49 publications
2
21
2
1
Order By: Relevance
“…Hack) either exposed to grazing by cattle, grazing by a native rodent, or protected from grazers by an exclosure for 20 years. In their study of sexual and clonal recruitment in Idaho fescue from a different Northem Great Basin Experimental Range pasture than ours,Liston et al (2003) also failed to detect any difference in genetic diversity at ISSR loci between plants sampled from inside and outside a grazing exclosure.Our negative result does not guarantee that grazing has had no affect on Idaho fescue during the 64 years the cattle exclosure has been in place at the Northern Great Basin Experimental Range. Other researchers have noted differences for Idaho fescue at NGBER between grazed and ungrazed sites.…”
contrasting
confidence: 73%
See 2 more Smart Citations
“…Hack) either exposed to grazing by cattle, grazing by a native rodent, or protected from grazers by an exclosure for 20 years. In their study of sexual and clonal recruitment in Idaho fescue from a different Northem Great Basin Experimental Range pasture than ours,Liston et al (2003) also failed to detect any difference in genetic diversity at ISSR loci between plants sampled from inside and outside a grazing exclosure.Our negative result does not guarantee that grazing has had no affect on Idaho fescue during the 64 years the cattle exclosure has been in place at the Northern Great Basin Experimental Range. Other researchers have noted differences for Idaho fescue at NGBER between grazed and ungrazed sites.…”
contrasting
confidence: 73%
“…For expected heterozygosity, we used the unbiased estimator described by Lynch and Milligan (1994) for dominant markers, including adherence to their recommendation of excluding all loci for which the null allele frequency was less than 3/N. Although Idaho fescue is a tetraploid, Liston et al (2003) observed disomic inheritance for allozyme loci in their study of Idaho fescue at NGBER. To calculate the allele frequencies necessary for estimating He, we assumed both disomic inheritance and that our samples were in Hardy-Weinberg equilibrium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proposed that ramet establishment is more efficient than genet establishment for the recruitment of new individuals of succulent species in arid environments (Arizaga and Ezcurra, 2002;Clark-Tapia et al, 2005;Liston et al, 2003). Furthermore, some authors (Allen et al, 1991;Mandujano et al, 1998Mandujano et al, , 2007 have observed that several Opuntia species in the Chihuahuan Desert undergo clonal propagation in highly stressful sites, such as intercanopy space, without the need for nurse plants.…”
Section: Introductionmentioning
confidence: 96%
“…Similar dates have been estimated for other clonal grasses (de Witte and St€ ocklin 2010). A more recent study with molecular markers suggested a minimum age for a plant of Festuca idahoensis as at least 60 years (Liston et al 2003).…”
Section: Asexual Reproductionmentioning
confidence: 99%